A novel joint transmission and caching optimizing scheme in multirelay networks: Video service quality assurance scheme. (2nd February 2017) - Liu, Bowen; Zhang, Heli; Ji, Hong; Li, Xi
Summary: The demands of instant video communication have recently increased as a means to improve user experience. Meanwhile, the cache mechanism has become an effective technology used in video transmission so that delay jitter could be reduced to a insignificant value. We propose a novel video service quality assurance scheme in multirelay networks (MRNs) with cache. Both wireless channel state information on the transmitting side and optimal receiver schemes on the receiving side are considered in the proposed scheme. We derive closed form expressions of video streaming for cache‐based MRN and investigate the impact of cache length when it is changed. Then, we proved that the optimal solution is difficult to acquire, and the suboptimal solution could be achieved by decomposing the original optimization problem into several simpler subproblems, which include graph and convex optimization. Specifically, we obtain a limit for the cache queuing model in MRNs. Detailed algorithms with corresponding theoretical reasoning are provided as well. Simulations demonstrate the effectiveness of our proposed scheme by comparing with some other existed high–video‐quality transmission schemes. The analysis also shows that our scheme outperforms others in jitter reducing. Abstract : This paper proposes a novel video service quality assurance scheme for multirelay networks with cache. We derive closed‐form expressions of video streaming for cache‐based multirelay network and investigate the impact of cache. Detailed algorithms with corresponding theoretical reasoning are provided as well. Simulations demonstrate the effectiveness of our proposed scheme by comparing with some other existing high–video quality transmission schemes. The analysis also shows that our scheme outperforms others in jitter reducing.